A comparative study of metal oxide and sulfate catalysts for selective catalytic reduction of NO with NH3. Issue 10 (19th May 2017) - Zhu, Lin; Zhong, Zhaoping; Yang, Han; Wang, Chunhua
ABSTRACT: The properties and characteristics of metal oxide and sulfate catalysts with different active elements for selective catalytic reduction of NO with NH3 were investigated. Cerium-based oxide catalyst showed the widest temperature window for NO x removal and manganese-based oxide catalyst exhibited the best catalytic performance at low temperature. For all the catalysts, the SCR activities at low temperature were directly related with the redox abilities of catalysts. The existence of sulfate groups inhibited the redox abilities of active species for sulfate catalysts compared with the metal oxide catalysts. The catalytic activities of CeWTi-S and MnWTi-S were seriously decreased in contrast to CeWTi-N and MnWTi-N. The temperature window of CuWTi-S was shifted toward higher temperature comparing with CuWTi-N. The FeWTi-N and FeWTi-S catalysts both showed high NO x conversion in the temperature range between 300°C and 400°C and N2 O concentrations for iron-based samples were least among the same kind of catalysts. The abundance of acid sites and weak stability of surface sulfate groups for iron- and copper-based sulfate catalysts might be the main reasons accounting for the better NO x conversion in the medium-temperature range.